Dispute Settlement between Indonesia and Australia on A4 Copy Paper AntiDumping Case by World Trade Organization (W.T.O.) - Illahi, Ridho; Jaya, Donna Azka Aviora; Nasywa, Siti Mahira; Firnaldi, Adrian (As- Sakinah Law Firm & Society of Visual Informatics, 2024)
The World Trade Organisation (WTO) has rendered the resolution of the A4 copy paperanti-dumping dispute between Indonesia and Australia a matter of worldwide significancein recent times. The dispute originated when Australia levied anti-dumping tariffs on A4copy paper imported from Indonesia. Consultations were conducted between Indonesia andAustralia, but, a consensus could not be achieved. Indonesia subsequently initiated legalproceedings before the World Trade Organisation (WTO), which ultimately rendered averdict in favour of Indonesia's claim against Australia for the imposition of an antidumping duty (BMAD) on A4 copy paper originating from Indonesia. An examination ofdispute settlement proceedings reveals that the World Trade Organisation (WTO) aims toguarantee that anti-dumping measures do not infringe against WTO regulations. Thisarticle will provide a detailed analysis of the World Trade Organisation (WTO) resolutionof the A4 copy paper anti-dumping conflict between Indonesia and Australia, and itsconsequences for international commerce.